2020
DOI: 10.24912/je.v24i3.609
|View full text |Cite
|
Sign up to set email alerts
|

Faktor-Faktor Non-Performing Financing (NPF) di Bank Umum Syariah Indonesia

Abstract: The bank's task is as an intermediary institution that is funding and lending. OJK Data shows that each year financing in Sharia banks continues to increase. Therefore sharia banking should prevent the minimum financing to occur and be obliged to know what the factors of the NPF are in order to maintain banking health. The purpose of this research is to know the NPF factors in Indonesia's Sharia bank. The research method used in this research is to use quantitative research with a double linear regression appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Therefore, it can be concluded that the capital adequacy ratio (CAR) is a bank performance ratio to measure the capital adequacy of the bank, to support assets containing or generating risks financed by own capital funds or sources of funds originating from outside the bank. Based on Asnani (2014) it is stated that CAR has a negative and significant effect on NPF. Therefore, the hypothesis proposed in this research is:…”
Section: Effect Of Car On Npfmentioning
confidence: 99%
“…Therefore, it can be concluded that the capital adequacy ratio (CAR) is a bank performance ratio to measure the capital adequacy of the bank, to support assets containing or generating risks financed by own capital funds or sources of funds originating from outside the bank. Based on Asnani (2014) it is stated that CAR has a negative and significant effect on NPF. Therefore, the hypothesis proposed in this research is:…”
Section: Effect Of Car On Npfmentioning
confidence: 99%
“…NPF is indeed an indicator of a bank's health (Ghoniyah and Hartono, 2020). If the NPF in a bank is higher, the level of risk that will be obtained will also be higher (Rofi'ah and A'yun, 2019). NPF height is strongly influenced by the bank's ability to execute with good credit granting process and in terms of credit management, including monitoring measures after the loans were disbursed and control measures when there are indications of irregularities or indications of defaulted loans.…”
Section: Introductionmentioning
confidence: 99%